O dever fundamental de pagar tributo no Estado Democrático de Direito - Almeida, Tiago de Lima (2019)
The present dissertation approaches the idea that the State materializes in a juridical-political organization, whose purpose is to protect and implement the values consecrated by the community, it analyzes the fundamental role of the tributes for the guarantee of the life in the modern society and for the promotion of the common good. Some duties, related to the very existence, concretization and maintenance of the State, are crowned by the Constitution with the status of fundamental ones, as is the case of the payment of tribute, main source of cost of public expenses. Through the analysis of the historical evolution of the State and the relations between it and the individuals, a precise understanding is made of the relation between the Democratic State of Law and the Fiscal State. It is not factually possible to establish a democratic state of law without the provision of the means necessary for its maintenance. It is a fundamental pillar for the Democratic State of Right to obtain resources able to meet and fulfill its objectives by which, even, it justifies its own creation. From this necessity arises the Fiscal State and the taxing power that materializes it. The work will address the exact scope of the individual's duty to pay tribute under the legitimation of a duty of social solidarity. In this perspective, the duty to pay tribute obligates all, who have the ability to contribute, to contribute with the State and, therefore, with the development of society delivering the same share of its wealth in a broad sense. The model of state that guarantees a free, just and solidary society, such as that drawn by the principles contained in the Constitution of the Federative Republic of Brazil, requires a counterpart on the part of the individuals that integrate such society, namely, the payment of tribute, which carries in its essence a constitutional duty opposable to all. The payment of taxes is a duty of the members of society, which guarantees the existence of the State and enables it to obtain means to achieve its ends, especially the guarantee and implementation of fundamental rights